Zeitschrift für Naturforschung A : A Journal of Physical Sciences (De Gruyter, 1946)
A Journal of Physical Sciences: Zeitschrift für Naturforschung A (ZNA) is an international scientific journal which publishes original research papers from all areas of experimental and theoretical physics. In accordance with the name of the journal, which means "Journal for Natural Sciences", manuscripts submitted to ZNA should have a tangible connection to actual physical phenomena.